Prediction of vibration characteristics using statistical energy analysis (SEA) - 180516 Mohd. Yunus Abdullah; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references